Effects of the inhibition of intestinal P‐glycoprotein on aliskiren pharmacokinetics in cynomolgus monkeys. (31st October 2014) - Tsukimoto, Mikiko; Ohashi, Rikiya; Torimoto, Nao; Togo, Yoko; Suzuki, Takashi; Maeda, Toshio; Kagawa, Yoshiyuki
Abstract Aliskiren is a substrate for P‐glycoprotein (P‐gp) and is metabolized via cytochrome P450 3A4 (CYP3A4). The aim of the present study was to assess whether P‐gp influenced the pharmacokinetics of aliskiren and also if drug–drug interactions (DDIs) mediated through P‐gp could be reproduced in cynomolgus monkeys. The study investigated the pharmacokinetics of aliskiren in mdr1a/1b gene‐deficient (P‐gp KO) and wild‐type (WT) mice. The area under the plasma concentration–time curve (AUC) following the oral administration of aliskiren was 6.9‐fold higher in P‐gp KO mice than in WT mice, while no significant differences were observed in the AUC or total plasma clearance following the intravenous administration of aliskiren to P‐gp KO mice. Then the pharmacokinetics of aliskiren were evaluated and DDIs between aliskiren and P‐gp inhibitors, such as cyclosporin A (CsA) and zosuquidar, examined in cynomolgus monkeys. The AUC for aliskiren were 8.3‐ and 42.1‐fold higher after the oral administration of aliskiren with the concomitant oral administration of zosuquidar and CsA at doses of 10 and 30 mg/kg, respectively. In contrast, the AUC after the intravenous and oral administration of aliskiren was not significantly affected by the oral administration of zosuquidar or intravenous administration of CsA, respectively. These results indicated that P‐gp strictly limited the intestinal absorption of aliskiren in mice and monkeys, and also that the effects of intestinal P‐gp inhibition by CsA or zosuquidar on the pharmacokinetics of aliskiren were sensitively reproduced in monkeys. In conclusion, aliskiren can be used as a sensitive substrate to evaluate intestinal P‐gp inhibition in monkeys. Copyright © 2014 John Wiley & Sons, Ltd.